Emosi Pada Tokoh Amy Dunne dalam Novel Gone Girl karya Gallian Flynn - Fitria Pharimita (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2023)
This research is entitled "Emotions of Amy Dunne's Character in Gillian Flynn's Gone Girl Novel". This study aims at identifying and describing the emotions experienced by the character Amy Dunne as well as the moral messages that could be drawn from the emotions she experiences. In analyzing the emotions of Amy Dunne's character in the novel Gone Girl, the author applies the theory of emotional classification according to Mashar and the theory of moral messages according to supported by (Nurgiyantoro, 2015). This study uses descriptive qualitative research methods, and data collection techniques using reading and note-taking techniques. The results showed that there are seven classifications of emotions, namely the concept of guilt, pent-up guilt, self-punishment, shame, sadness, hatred, and love, the author only found three types of emotion classification, namely the emotions of hatred, sadness, and love, while the moral message that could be taken from the novel Gone Girl by Gillian Flynn, the author finds that the moral message is conveyed indirectly through the characteristics of the characters Nick Dunne and Amy Dunne who are a husband and wife, namely disrespect.